Psychosocial support of nurses working in the frontline during COVID-19 pandemic in Tshwane District, Gauteng Province - Mulaudzi, Fhumulani Mavis (University of Pretoria, 2022)
Dissertation (MCur (Clinical))--University of Pretoria, 2021.